Comparative Analysis of the Secretome and Interactome of Trypanosoma cruzi and Trypanosoma rangeli Reveals Species Specific Immune Response Modulating Proteins - Watanabe Costa, Renata; Batista, Marina Ferreira; Meneghelli, Isabela; Vidal, Ramon Oliveira; Nájera, Carlos Alcides; Mendes, Ana Clara; Andrade-Lima, Izabela Augusta; da Silveira, José Franco; Lopes, Luciano Rodrigo; Ferreira, Ludmila Rodrigues Pinto; Antoneli, Fernando; Bahia, Diana (Frontiers in Immunology, 2020)
Chagas disease, a zoonosis caused by the flagellate protozoan Trypanosoma cruzi, is a chronic and systemic parasitic infection that affects approximately 5-7 million people worldwide, mainly in Latin America. Chagas disease is an emerging public health problem due to the lack of vaccines and effective treatments. According to recent studies, several T. cruzi secreted proteins interact with the human host during cell invasion. Moreover, some comparative studies with T. rangeli, which is non-pathogenic in humans, have been performed to identify proteins directly involved in the pathogenesis of the disease. In this study, we present an integrated analysis of canonical putative secreted proteins (PSPs) from both species. Additionally, we propose an interactome with human host and gene family clusters, and a phylogenetic inference of a selected protein. In total, we identified 322 exclusively PSPs in T. cruzi and 202 in T. rangeli. Among the PSPs identified in T. cruzi, we found several trans-sialidases, mucins, MASPs, proteins with phospholipase 2 domains (PLA2-like), and proteins with Hsp70 domains (Hsp70-like) which have been previously characterized and demonstrated to be related to T. cruzi virulence. PSPs found in T. rangeli were related to protozoan metabolism, specifically carboxylases and phosphatases. Furthermore, we also identified PSPs that may interact with the human immune system, including heat shock and MASP proteins, but in a lower number compared to T. cruzi. Interestingly, we describe a hypothetical hybrid interactome of PSPs which reveals that T. cruzi secreted molecules may be down-regulating IL-17 whilst T. rangeli may enhance the production of IL-15. These results will pave the way for a better understanding of the pathophysiology of Chagas disease and may ultimately lead to the identification of molecular targets, such as key PSPs, that could be used to minimize the health outcomes of Chagas disease by modulating the immune response triggered by T. cruzi infection.